2018
DOI: 10.1039/c8sm01258j
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation around a heated colloid in bulk and under confinement

Abstract: We study the non-equilibrium coarsening dynamics of a binary liquid solvent around a colloidal particle in the presence of a time-dependent temperature gradient that emerges after a temperature quench of a suitable coated colloid surface. The solvent is maintained at its critical concentration and the colloid is fixed in space. The coarsening patterns near the surface are shown to be strongly dependent on the colloid surface adsorption properties and on the temperature evolution. The temperature gradient alter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Recently, there have been numerous studies of directional quenching [20,[25][26][27][28][29][30][31][32][33]. In previous work, we reported formation of a large length-scale periodic pattern using a radial quench [27]; we also showed that the width of the lamellae can be controlled using V in a three-dimensional numerical simulation with parameters which replicated realistic experimental conditions [32].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Recently, there have been numerous studies of directional quenching [20,[25][26][27][28][29][30][31][32][33]. In previous work, we reported formation of a large length-scale periodic pattern using a radial quench [27]; we also showed that the width of the lamellae can be controlled using V in a three-dimensional numerical simulation with parameters which replicated realistic experimental conditions [32].…”
Section: Introductionsupporting
confidence: 53%
“…Directional quenching may also be seen in experimental systems. For example, when a system with particle inclusions is quenched, phase separation is seen to occur near the particles first since they have a greater heat conductivity, creating a temperature front [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…15 Deeper quenches have been studied only for homogeneously heated particles. 16 This has motivated us to combine experiment and theory in order to investigate the non-equilibrium coarsening dynamics around a hot spherical Janus particle suspended in a binary solvent. This is a challenging task because of technical limitations of both approaches.…”
Section: Introductionmentioning
confidence: 99%
“…We find that v remains rather constant and very close to the speed far away from the wall. A reduction in v is observed only during the detachment from the wall, which is possibly due to phoretic interactions induced by the concentration gradient adjacent to the capped hemisphere when the particle cap faces the wall surface [48]. Therefore, in a Newtonian fluid the interaction between the AP and the wall surface is mainly mediated by steric forces and to a lesser extent by hydrodynamic effects.…”
Section: Aps Near a Flat Wallmentioning
confidence: 97%